Post-Covid-19 Clinical Findings: A case report (Research, Society and Development, 2023)
Aim: The aim of this article was to analyze the clinical profile of two patients, three months after contracting Covid-19. Methods: It refers to a descriptive case series study, containing two samples. The tools used to draw this clinical profile were spirometry and dynamometry, in addition to questionnaires to assess quality of life, dyspnea, post-Covid-19 functionality, perception of global effect, objective function, cognitive failures, numerical visual scale, pain questionnaire McGill, pain catastrophizing scale and numerical visual scale, correlating them with findings found in the literature. Results: As a result, the variables pain and cognitive impairment are unanimously observed as sequelae of the disease. Conclusion: It is concluded that the changes in patients who had a previous infection with Covid-19 are important and considerable in terms of spirometry results, muscle weakness, changes in quality of life and deficits in objective function. As well as patients with post Covid-19 pain have levels of anxiety and kinesiophobia.